2019
DOI: 10.1111/and.13308
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the relationship between BRCA1 and BRCA2 genes methylation profile and sperm DNA fragmentation in infertile men

Abstract: The purpose of the study was to investigate whether the promoter methylation status of BRCA1 and BRCA2 DNA repair genes is associated with sperm DNA fragmentation (sDF) in infertile men with oligoasthenoteratozoospermia (OAT) which emerges due to various reasons and is effective in male infertility. Seventy‐three infertile men with OAT and 20 normozoospermic volunteers participated in the study. To investigate sDF and methylation patterns of BRCA1 and BRCA2 gene promoters, TUNEL assay and methylation‐specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…High methylation levels of the DNA repair X-ray repair cross-complementing protein 1 gene have been found in OAT males, thereby suggesting that the improper methylation of this gene may have a role in sperm chromatin condensation and OAT (Metin Mahmutoglu et al, 2021). Contrariwise, two additional well-known DNA repair genes, i.e., breast cancer type 1 susceptibility protein (BRCA1) and BRCA2, did not show defective methylation in infertile men with OAT (Kabartan et al, 2019). Several other genes found aberrantly methylated in altered sperm samples from infertile males have been investigated at a single-study level (Table 1).…”
Section: Gene Methylation Changesmentioning
confidence: 97%
“…High methylation levels of the DNA repair X-ray repair cross-complementing protein 1 gene have been found in OAT males, thereby suggesting that the improper methylation of this gene may have a role in sperm chromatin condensation and OAT (Metin Mahmutoglu et al, 2021). Contrariwise, two additional well-known DNA repair genes, i.e., breast cancer type 1 susceptibility protein (BRCA1) and BRCA2, did not show defective methylation in infertile men with OAT (Kabartan et al, 2019). Several other genes found aberrantly methylated in altered sperm samples from infertile males have been investigated at a single-study level (Table 1).…”
Section: Gene Methylation Changesmentioning
confidence: 97%
“…ling step, terminal deoxynucleotidyl transferase (TdT) enzyme was utilised for adding fluorescein isothiocyanate-deoxyuridine triphosphate (FITC-dUTP) to 3'-hydroxyl (OH) ss-and dsDNA break sites. In the last step of the TUNEL assay, spermatozoa were counterstained with an anti-fade including DAPI(Kabartan et al, 2019). A negative control without TdT enzyme and a positive control pre-treated with 200 mM H 2 O 2 for an hour were employed in each run.Slides were immediately visualised under a fluorescent microscope at 400X magnification (Olympus BX-51).…”
mentioning
confidence: 99%
“…DNA fragmentation may result from various exogenous factors including cigarette smoking, varicocele, cancer, irradiation and advanced age Kabartan et al, 2019) and has been proposed to be specifically associated with elevated levels of male infertility and pregnancy loss (Zini et al, 2001). Germ cells have various DNA repair mechanisms to protect the genomic integrity and to provide the full transmission of genetic information to the next generations properly (González-Marín et al, 2012;Gunes et al, 2015).…”
mentioning
confidence: 99%
“…Other studies, in contrast, found no association between aberrant DNA methylation of PEG1/MESTand oligozoospermia (Marques et al, 2004). Kabartan et al (2019) found no association between oligozoospermia and DNA methylation of breast cancer gene 1 and 2 (BRCA1 and BRCA2). Tang et al (2018) found that male subfertility, whether or not semen samples were oligozoospermic, was associated with DNA methylation defects in imprinted genes, including H19.…”
Section: Evidence For the Association Between Spermatozoal Dna Methylation And Male Subfertility Including Abnormal Semen Parametersmentioning
confidence: 81%